Identificación de viremia primaveral de la carpa (VPC) carassius auratus en São Paulo, Brasil - ALENXANDRINO, AGAR COSTA; Ranzani-Paiva, Maria José Tavares; Romano, Luis Alberto (Revista Ceres, 2015)
-